APLIKASI SISTEM PAKAR DIAGNOSIS KERUSAKAN HARDWARE KOMPUTER DENGAN METODE FORWARD CHAINING - Arifin, Samsul (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2012)
Not all owners and computer technicians can diagnose early damage to computer hardware properly and appropriately. Errors in the diagnosis process will certainly bring harm to the owner of a computer or computer technicians. Based on these facts, researchers designed a diagnostic expert system computer hardware damage, in the hope of this expert system can assist them in diagnosing damage to computer hardware like an expert.In damage to computer hardware, the symptoms appear can not be used to determine the exact damage to computer hardware. These symptoms should be collected and to match each other, so that it can generate the appropriate conclusions. This process is called in an expert system by the method of forward chaining.The process of diagnosis expert system with forward chaining method can work well, the expert system application interface that is easy to use and informative, enabling the user to use and understand the contents of the information submitted in the application of expert system. Keywords : Expert systems, hardware damage, Forward Chaining